Hemodynamic status of patients with different comorbidities of ischemic heart disease before and after coronary artery bypass grafting - B. I. Geltser; E. A. Sergeev; V. N. Kotelnikov; A. A. Silaev; R. S. Karpov (Бюллетень сибирской медицины, 2021)
Aim. To assess the hemodynamic status by transpulmonary thermodilution (TPTD) in patients with ischemic heart disease (IHD) with different comorbidities before and after coronary artery bypass grafting (CABG).Materials and methods. 66 patients with IHD (40 men and 26 women) aged 53 to 77 years who were admitted for planned CABG were examined. The patients were divided into three groups according to the comorbidity: cardiovascular, respiratory, and metabolic. The first comorbidity was represented by a combination of IHD and multifocal atherosclerosis, the second – by IHD and chronic obstructive pulmonary disease (COPD), and the third – by IHD and metabolic syndrome (MS). All patients underwent CABG with the use of cardiopulmonary bypass. Hemodynamic parameters were recorded by the TPTD method using the Pulsion Picco Plus module (Germany) at 3 stages: after the start of mechanical ventilation (stage I), after the completion of cardiopulmonary bypass (stage II), and 24 hours after CABG (stage III).Results. The patients with IHD with different comorbidities differed in characteristic signs of hemodynamic changes. In IHD with comorbid COPD, after withdrawal from the cardiopulmonary bypass and 24 hours after CABG, the highest index of systemic vascular resistance, the minimum values of the global ejection fraction, and a decrease in the global end-diastolic volume and pulmonary blood volume less noticeable compared with other groups of patients were noted. With comorbid respiratory and metabolic disorders, the maximum values for the indices of extravascular lung water and pulmonary vascular permeability were recorded. In the patients with a comorbid cardiovascular disease, hemodynamic and volume status violations in the dynamic follow-up were less pronounced.Conclusion. The use of the TPTD method in patients with IHD before and after CABG makes it possible to specify the functional state of the circulatory system in different comorbidities, which increases the effectiveness of risk stratification and the accuracy of predicting possible complications.